2014
DOI: 10.1088/1674-1056/23/2/027503
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias in ferromagnet/antiferromagnet bilayers

Abstract: Since the exchange bias (EB) effect was discovered in the Co/CoO core-shell nanoparticles, it has been extensively studied in various ferromagnet (FM)/antiferromagnet (AFM) bilayers due to its crucial role in spintronics devices. In this article, we review the investigation of the EB in our research group. First, we outline basic features of the EB, including the effects of the constituent layer thickness, the microstructure and magnetization of the FM layers, and we also discuss asymmetric magnetization rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 97 publications
1
23
0
1
Order By: Relevance
“…Interestingly, both parameters show nonmonotonic trend with d AFM , as they exhibit a maximum for CS9 ( d AFM = 5 nm) and a subsequent decay to a value that remains constant for the two larger samples (CS15 and CS18). Regarding H E , its dependence is in good agreement with that theoretically predicted , and experimentally observed ,, in AFM|FM bilayers. The nonmonotonic dependence is described by considering the concomitant effect of the energy barrier of the AFM material ( K AFM V AFM ) and the formation and growth of AFM domains, which are responsible for the onset and the maximum of H E , respectively. , However, due to the reduced volume of our CS NPs, the formation and growth of AFM domains appears rather unlikely.…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, both parameters show nonmonotonic trend with d AFM , as they exhibit a maximum for CS9 ( d AFM = 5 nm) and a subsequent decay to a value that remains constant for the two larger samples (CS15 and CS18). Regarding H E , its dependence is in good agreement with that theoretically predicted , and experimentally observed ,, in AFM|FM bilayers. The nonmonotonic dependence is described by considering the concomitant effect of the energy barrier of the AFM material ( K AFM V AFM ) and the formation and growth of AFM domains, which are responsible for the onset and the maximum of H E , respectively. , However, due to the reduced volume of our CS NPs, the formation and growth of AFM domains appears rather unlikely.…”
Section: Resultssupporting
confidence: 89%
“…The EB effect was discovered in 1956 by Meiklejohn and Bean in Co/CoO nanoparticles1, and has been extensively studied and explored in various systems including FM-AFM nanocomposite/bilayers2, spin glass (SG)-FM structures3, and more45. These systems have significant applications in ultrahigh-density magnetic recording, giant magnetoresistance, and spin valve devices678.…”
mentioning
confidence: 99%
“…1 In thin-film exchange-biased systems, it has been shown that the magnitude of the exchange bias is conditional on the relative thicknesses of each thin-film layer; exchange bias is known to be inversely proportional to the FM thickness (reaching a maximum at sub-10 nm film thicknesses). 3,4 The role of the AF thickness on exchange bias is much more complex. 1,3,4 While studied extensively in oxide-coated particles and two-dimensional (2D) bilayer thin-film systems, research into the exchange-bias effect in bulk nanocomposite systems has been limited.…”
Section: Introductionmentioning
confidence: 99%